2011
DOI: 10.19030/jabr.v16i3.2043
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Self-Efficacy, Assertive-ness, Stress, And Gender On Intention To Turnover In Public Accounting

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt;"><span style="font-family: Batang; font-size: x-small;">The purpose of this study is to examine the effects of these variables on intention to turnover among public accountants, and to suggest ways to improve retention of both male and female accountants in public practice.<span style="mso-spacerun: yes;">&nbsp; </span>Results indicate that self-efficacy had a direct, positive relationship with male public accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Concerning the latter, the suggestion is employees were more likely to state a leave intention when they had high self-efficacy. Despite being the opposite of what was expected and thus contradicting Lewin and Sager (2010), the finding confirms a study conducted by Troutman et al (2000). But, it is important to note that the latter study only found that to be the case among men.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Concerning the latter, the suggestion is employees were more likely to state a leave intention when they had high self-efficacy. Despite being the opposite of what was expected and thus contradicting Lewin and Sager (2010), the finding confirms a study conducted by Troutman et al (2000). But, it is important to note that the latter study only found that to be the case among men.…”
Section: Discussionsupporting
confidence: 63%
“…Still, another explanation centers on differences in populations. For instance, Lewin and Sager (2010) focused on salespersons; Troutman et al (2000) examined accountants; and this one, government employees. The differences could thus be due to the populations sampled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence assertiveness may facilitate access to mates and increase chances of mating. Specifically, action-oriented characteristics and sociality (e.g., willingness to take a stand and dominance) and the willingness to face new challenges may prompt individuals to actively initiate sexual expression and seek out an available mate (Hromatko, Tadinac, & Vranic, 2008;Troutman, Burke, & Beeler, 2000).…”
mentioning
confidence: 99%